If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 237 = 4x + 172 Reorder the terms: 237 + 9x = 4x + 172 Reorder the terms: 237 + 9x = 172 + 4x Solving 237 + 9x = 172 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 237 + 9x + -4x = 172 + 4x + -4x Combine like terms: 9x + -4x = 5x 237 + 5x = 172 + 4x + -4x Combine like terms: 4x + -4x = 0 237 + 5x = 172 + 0 237 + 5x = 172 Add '-237' to each side of the equation. 237 + -237 + 5x = 172 + -237 Combine like terms: 237 + -237 = 0 0 + 5x = 172 + -237 5x = 172 + -237 Combine like terms: 172 + -237 = -65 5x = -65 Divide each side by '5'. x = -13 Simplifying x = -13
| 4(y-2)-9=-7(-2y+5)-2y | | 11-w/2=60 | | 4x(5x+7)= | | ax^2+6ax+9a=0 | | -x+15-3x+6=-7x-4x | | (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 | | (78x-48y)-(68x+28y)= | | -x+5y-3x-2y= | | 4(5y+7z)-28z= | | 5/13+6/11 | | 2(6y+2z)-4z= | | k+-9k-8k-10k=-20 | | 5y(2y-4)+14y= | | 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= |